2017
DOI: 10.1111/fcp.12303
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with melatonin protects against cyclophosphamide‐induced oxidative stress and renal damage in mice

Abstract: Cyclophosphamide (CP) is widely used in treatment of different cancers. Nephrotoxicity is one of the dose-limiting side effects of CP. This study was carried out to investigate the effect of melatonin (MEL) on CP-induced nephrotoxicity in mice. In this study, 50 Swiss albino mice (20-25 g) were randomly divided into five groups. Mice were pretreated with MEL intraperitoneally (i.p) in doses of 5, 10 and 20 mg/kg for five consecutive days, and CP (200 mg/kg, i.p) was administrated on the 5th day 1 h after the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 53 publications
2
30
0
2
Order By: Relevance
“…The data are in line with previous studies indicating that melatonin prevented LPO and ROS overproduction induced by acrylamide in PC12 cells [30]. It is also indicated that melatonin decreased LPO and reversed the cyclophosphamideinduced oxidative stress and nephrotoxicity in mice [31].…”
Section: Discussionsupporting
confidence: 92%
“…The data are in line with previous studies indicating that melatonin prevented LPO and ROS overproduction induced by acrylamide in PC12 cells [30]. It is also indicated that melatonin decreased LPO and reversed the cyclophosphamideinduced oxidative stress and nephrotoxicity in mice [31].…”
Section: Discussionsupporting
confidence: 92%
“…The present data thus indicate that SCHPs-F1 treatment significantly relieved CTX-induced renal oxidative stress, inflammatory responses, and apoptosis in mice, likely by enhancing the antioxidant protective system comprising GSH-Px, SOD, CAT, and T-AOC, and by suppressing the lipid peroxidation product MDA, the pro-inflammatory cytokines IL-1β, IL-6, TNF-α and IFN-γ, and the pro-apoptotic Bax/Bcl-2 ratio. It is known that acrolein has a severe adverse effect on the kidneys, which results in the robust activation of oxidative stress responses and further aggravation of renal injury [1,30,31]. GSH-Px, SOD, CAT, and T-AOC are critical indicators for evaluating the capacity of the cellular antioxidant defense system [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…GSH-Px, SOD, CAT, and T-AOC are critical indicators for evaluating the capacity of the cellular antioxidant defense system [32,33]. An imbalance in oxidative stress defense leads to insufficient antioxidant responses and lipid peroxidation to generate MDA [31,34]. As mentioned, SCHPs-F1 increased the antioxidant defense parameters GSH-Px, SOD, CAT, and T-AOC and decreased levels of the lipid peroxidation marker MDA, thereby potentially alleviating oxidative stress of CTX-exposed kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress induces protein oxidation, DNA oxidation, and mitochondrial damage. ROS activity is balanced in the body by an antioxidant defense system (ADS), the main components of which are antioxidants and antioxidant enzymes . Depending on their operation, free radical production is substantially decreased, and that already formed are converted into O 2 or H 2 O.…”
Section: Introductionmentioning
confidence: 99%